(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article investigates the influence of the writers, who come from the Polish-Ukrainian frontier, on the development of Polish literature. It is defined that the literature of the Polish-Ukrainian frontier became peculiar basis for the emergence of Ukrainian language school in Polish romanticism. Some peculiarities of the Ukrainian language usage in Polish literature are clarified. The specificity of the Ukrainian borrowings’ usage and their impact on the phonetic system and vocabulary of the Polish language is also revealed.